Toxicity assessment of individual ingredients of synthetic-based drilling muds (SBMs) - Bakhtyar, Sajida; Gagnon, Marthe Monique (Springer Netherlands, 2012)
Synthetic-based drilling muds (SBMs) offer excellent technical characteristics while providing improved environmental performance over other drilling muds. The low acute toxicity and high biodegradability of SBMs suggest their discharge at sea would cause minimal impacts on marine ecosystems, however, chronic toxicity testing has demonstrated adverse effects of SBMs on fish health. Sparse environmental monitoring data indicate effects of SBMs on bottom invertebrates. However, no environmental toxicity assessment has been performed on fish attracted to the cutting piles. SBM formulations are mostly composed of synthetic base oils, weighting agents, and drilling additives such as emulsifiers, fluid loss agents, wetting agents, and brine. The present study aimed to evaluate the impact of exposure to individual ingredients of SBMs on fish health. To do so, a suite of biomarkers [ethoxyresorufin-O-deethylase (EROD) activity, biliary metabolites, sorbitol dehydrogenase (SDH) activity, DNA damage, and heat shock protein] have been measured in pink snapper (Pagrus auratus) exposed for 21 days to individual ingredients of SBMs. The primary emulsifier (Emul S50) followed by the fluid loss agent (LSL 50) caused the strongest biochemical responses in fish. The synthetic base oil (Rheosyn) caused the least response in juvenile fish. The results suggest that the impact of Syndrill 80:20 on fish health might be reduced by replacement of the primary emulsifier Emul S50 with an alternative ingredient of less toxicity to aquatic biota. The research provides a basis for improving the environmental performance of SBMs by reducing the environmental risk of their discharge and providing environmental managers with information regarding the potential toxicity of individual ingredients. © 2011 Springer Science+Business Media B.V.